The effects of intensive dietary weight loss and exercise on gait in overweight and obese adults with knee osteoarthritis. The Intensive Diet and Exercise for Arthritis (IDEA) trial. (2nd January 2020) - Messier, Stephen P.; Beavers, Daniel P.; Mihalko, Shannon L.; Miller, Gary D.; Lyles, Mary F.; Hunter, David J.; Carr, J. Jeffery; Eckstein, Felix; Guermazi, Ali; Loeser, Richard F.; DeVita, Paul
Abstract: The Intensive Diet and Exercise for Arthritis (IDEA) trial was an 18-month randomized controlled trial that enrolled 454 overweight and obese older adults with symptomatic and radiographic knee osteoarthritis (OA). Participants were randomized to either exercise (E), intensive diet-induced weight loss (D), or intensive diet-induced weight loss plus exercise (D + E) interventions. We previously reported that the clinical benefits of D + E were significantly greater than with either intervention alone (e.g., greater pain reduction, and better function, mobility, and health-related quality of life). We now test the hypothesis that D + E has greater overall benefit on gait mechanics compared to either intervention alone. Knee joint loading was analyzed using inverse dynamics and musculoskeletal modeling. Analysis of covariance determined the interventions' effects on gait. The D + E group walked significantly faster at 18-month follow-up (1.35 m s −1 ) than E (1.29 m s −1, p = 0.0004) and D (1.31 m s −1, p = 0.0007). Tibiofemoral compressive impulse was significantly lower (p = 0.0007) in D (1069 N s) and D + E (1054 N s) compared to E (1130 N s). D had significantly lower peak hip external rotation moment (p = 0.01), hip abduction moment (p = 0.0003), and peak hip power production (p = 0.016) compared with E. Peak ankle plantar flexion moment was significantly less (p < 0.0001) in the two diet groups compared with E. There also was a significant dose-response to weight loss; participants that lost >10% of baseline body weight had significantly (p = 0.0001) lower resultant knee forces and lower muscle (quadriceps, hamstring, and gastrocnemius) forces than participants that had less weight loss. Compared to E, D produces significant load reductions at the hip, knee, and ankle; combining D with E attenuates these reductions, but most remain significantly better than with E alone.